DSP-based ADI-PML formulations for truncating linear Debye and Lorentz dispersive FDTD domains - Ramadan, O (Springer-Verlag Berlin, 2005)
An efficient and unconditional stable formulations of the perfectly matched layer (PML) are presented for truncating linear Debye and Lorentz dispersive Finite Difference Time Domain (FDTD) grids. The formulations incorporate the Digital Signal Processing algorithms developed for digital filters into the Alternating Direction Implicit FDTD method. Numerical examples are included to validated the proposed formulations.
International Conference on Computational Science and Its Applications (ICCSA 2005) -- MAY 09-12, 2005 -- Singapore, SINGAPORE
Keywords: Perfectly Matched Layer; Media; Implementation